Long-term outcomes in patients after COVID-19: data from the TARGET-VIP registry - M. M. Lukyanov; N. P. Kutishenko; S. Yu. Martsevich; A. A. Pulin; E. Yu. Andreenko; V. P. Voronina; V. A. Dindikova; N. A. Dmitrieva; O. V. Lerman; A. N. Makoveeva; E. Yu. Okshina; A. S. Sgibneva; et al. (Российский кардиологический журнал, 2022)
Aim. To assess long-term outcomes within 12 months after hospital treatment of patients with coronavirus disease 2019 (COVID-19) as part of a prospective registry.Material and methods. Outcomes in the posthospital period were assessed in 827 patients diagnosed with COVID-19 (age, 58,0±14,8 years; men, 51,3%). For periods of 30-60 days, 6 and 12 months after discharge from the hospital, cases of death, nonfatal myocardial infarction (MI) and stroke, hospitalization, acute respiratory viral infections/influenza were assessed. The follow-up period was 13,0±1,5 months.Results. During the follow-up period, 35 (4,2%) patients died, 6 (0,73%) and 4 (0,48%) cases of MI and stroke were registered. In addition, 142 (17%) patients were hospitalized, while 217 (26,2%) patients had acute respiratory viral infections/ influenza. Factors of age and length of intensive care unit stay were significantly associated (p<0,001) with the risk of all-cause death (hazard ratio (HR)=1,085 per 1 year of life and HR=6,98, respectively), with the risk of composite endpoint (death, non-fatal MI and stroke): HR=1,081 per 1 year of life and HP=4,47. Of the 35 deaths, 11 (31%) were within the first 30 days of follow-up, and 19 (54%) — 90 days after discharge from the hospital. A higher probability of hospitalization was associated with older age (odds ratio (OR)=1,038; p<0,001), while a higher probability of acute respiratory viral infections/influenza was associated with younger age (OR=0,976 per 1 year of life; p<0,001) and female sex (OR=1,414; p=0,03).Conclusion. A prospective follow-up of 827 patients in the TARGET-VIP registry revealed that 12-month mortality was 4,2%, while more than half of the deaths (54%) were registered in the first 90 days, including 31% — for the first month after discharge from the hospital. The most common events were hospitalizations (17,0%) and acute respiratory viral infections/influenza (26,2%), while the rarest were myocardial infarction (0,73%) and stroke (0,48%). The key factors associated with 12-month mortality in the post-COVID-19 period were older age and intensive care unit stay during the reference hospitalization. A higher readmission rate during the follow-up period was associated with older age, and the prevalence of acute respiratory viral infections /influenza during the follow-up period was associated with younger patients and female sex.